Peat swamp frogs of Borneo - Robert F, Inger; Robert B, Stuebing; Ramlah, Zainudin (Academia Publisher, 2005)
The frog fauna of peat swamps in Borneo has been little studied,which may at least partlyaccount for the small known size of this fauna.Yet the areal extent and wide distribution of this habitatin Sundaland suggest that it may be an important habitat for a segment of the Sundaland fauna.Remnants of peat swamps have been discovered at a number of submarine sites and dated at agesbetween 40,000 and 3,500 yBP.These discoveries indicate that peat swamps may have been importantdispersal routes for some species of frogs during periods of regression of the South China Sea.Thispotential for Pleistocene dispersal may explain the low level of endemism within the peat swampassemblage of frog species.